Efektivitas Model Pembelajaran Kooperatif Tipe NHT dan Talking Stick Berbantu Prezi terhadap Prestasi Belajar Siswa - Syan Risnanda; Muhtarom Muhtarom; Sutrisno Sutrisno (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2019)
Student learning achievement in mathematics lessons and using learning models are still low and not in accordance with the material. The use of models in learning must be adapted to the material to achieve satisfactory student achievement. This type of research is quantitative and aims to determine the effectiveness of learning using the Taking Stick model and Prezi's NHT assisted model on student learning achievement. The population of this research is class VII students of SMP Negeri 29 Semarang in the academic year 2017/2018. Sampling using cluster random sampling technique so that three classes were obtained randomly, namely VII A, VII B, and VII C. The design of this study was the Posttest Only Control Design. Data obtained through multiple choice test results were then processed by ANAVA test, Sceffe Test, learning completeness test and simple linear regression test. Data analysis results show that (1) there are differences in student achievement using Prezi-assisted Taking Stick learning models, Prezi-assisted NHT learning models and conventional learning models. (2) Students' learning achievement using Prezi-assisted Taking Stick models is better than conventional learning models. (3) Learning achievement of students who use Prezi-assisted NHT models is better than conventional learning models. (4) Learning achievements of students who use the Taking Stick model and Prezi-assisted NHT achieve KKM. (5) There is a correlation between student activity and learning achievement for classes that receive Prezi Talking Stick learning model and classes that receive Prezi's NHT assisted learning model.